Progress on the Fifteenth General Review of Quotas-Report of the Executive Board to the Board of Governors (April 2019). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2021)
Following the guidance on the Board of Governors Resolution No. 72-1 (December 2016), on April 3, 2019, the Executive Board discussed and adopted its fourth semi-annual report on progress on the Fifteenth Review. The report described that it had become evident that it would not be possible to secure the required support for a quota increase under the Fifteenth Review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet